Modelling and simulation of predictive handover control mechanisms for fast moving mobile nodes in wireless networks. (2016) - Goyal, Raman Kumar; Kaushal, Sakshi
When a mobile node (MN) is moving at a high speed from one network to another network, internet connectivity is degraded as MN cannot complete the handover within the required time owing to delayed triggering of handover request. To ensure seamless connectivity without performance degradation, traditional handover mechanism needs to be enhanced. In this paper, a media independent handover (MIH)-based handover triggering scheme is proposed based on the mobility prediction of MN. Handover triggering is predicted by calculating link expiration time that depends on velocity, direction and distance of MN from the access point. Scanning process required for traditional MIH networks is eliminated using information server (IS) that estimates the received signal strength (RSS) of candidate networks based on the location of MN. Simulation results show that the proposed scheme reduces the handover latency and improves the throughput in homogenous networks at varying velocities of MN.